CONDITIONS FOR SUCCESS IN APOLOGY SPEECH GENRE - Oleksandra M. Shumiatska (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2021)
The article investigates the linguo-pragmatic conditions of the speech genre of apology in modern German. The purpose of the research is a comprehensive analysis of the examined speech genre. The main task is to identify and describe the conditions for the success of apology in German linguistic culture. To achieve a certain goal and solve the tasks, a number of methods have been applied: logical-semantic – to identify formal, semantic and functional parameters of apology; descriptive method – to characterize the typical linguistic means of apology; comparative analysis – to compare apologies with related speech acts; pragma-semantic method – to identify communicative strategies and tactics of apology; transactional method – for the analysis of verbal and nonverbal behavior of participants of communication; intent-analysis – to identify an indirect apology; method of quantitative calculations – for the implementation of quantitative characteristics of the use of apologies in German; questionnaire method – to confirm ethno-specific signs of forgiveness in German linguistic culture. Since in the proposed study the speech genre (hereinafter SG) is considered a set of SA with a common illocutionary goal to apologize to the interlocutor for the negative act committed by the speaker, the basis for success of the SG of apology constitutes the parameters of successful implementation of SA of apology. However, we consider it expedient to pay additional attention to external factors of SG realization, semantics and syntax of linguistic means of expression of the studied SG, as well as the pragmatics of creation and perception of SG by communicators. In view of apology in terms of its success, we believe that the most important thing for its implementation is the condition of sincerity, which is directly related to such components as malefactive action, guilt, pity (repentance), request, positive reaction of the addressee. Having committed a malefactive action, the speaker realizes his guilt, feels sorry for what he did, and asks the interlocutor for apology. A positive reaction of the addressee is also a necessary condition for the success of apology, i.e. the addressee must accept the speaker’s apology, otherwise the SG will fail and the communicative goal (restoration of harmony in the relationship) will not be achieved. The condition of sincerity of the SG of apology may include the following components: 1) the speaker actually believes that he has committed or intends to commit a malefactive action in relation to his interlocutor; 2) the addressee actually admits his guilt; 3) the speaker feels psychological discomfort and sincerely regrets the damage caused; 4) the addressee apologizes to the listener for his misconduct; 5) the addressee accepts the apology of the speaker and forgives his guilt. Based on the results of the analysis, the following conditions for the success of the speech genre of apology are formulated: 1) fulfillment of the condition of sincerity; 2) knowledge of the rules of polite behavior in the relevant cultural environment; 3) the presence of general knowledge about the situation; 4) compliance with the principles of speech cooperation; 5) analysis and planning of one’s behavior and the behavior of the interlocutor. It was found that the success or failure of apology can be assessed by analyzing the perlocutionary effect, and violation of the conditions of success can lead to communicative failure, which manifests itself in a negative reaction of the addressee and hinders cooperative interpersonal communication.